Study of incidence and risk factors of urinary tract infection in catheterised patients admitted at tertiary care - Kakaria, Bhavana Ashish; K., Ashish; Tushar, Raghuwanshi (International Journal of Research in Medical Sciences, 2018)
Background: Catheter-associated urinary tract infections (CAUTIs) are the most common nosocomial infection and a leading cause of morbidity and mortality in hospitalized patients. The aim of this study was to determine the incidence and risk factors of urinary tract infection in catheterised patients in a tertiary care hospital. Methods: Total of 200 patients above 16 years in whom an indwelling Foley‘s catheter inserted were taken in the study. A urine specimen was obtained aseptically and culture done on nutrient agar, sheep blood agar and MacConkey agar plates. After incubation of 24 hours, colony count done for organisms showing growth and colony count ≥105 was taken significant. Results: The incidence of CAUTI in the present study was 31%. Higher incidence of CAUTI (56.46%) was found in female sex as compared to males (43.54%). Incidence of CAUTI was found higher in first weeks (54.83%). Incidence among diabetes patients is found more (63.33%). Most common isolate found was E. coli (38.71%) among all uropathogens. Uropathogens isolated from CAUTI are more resistant to antimicrobials. Conclusions: It is must to implement following strategy for reducing the risk of infection due to indwelling catheters: 1. reducing the duration of catheterization 2. Use antibacterial substance coated catheter 3. Strict infection control measures.